Teaching Practice in the Process of Future Teachersʼ Training to do Educational work at Primary School - Tytun, Oksana (Pedagogical Discourse, 2015)
The article deals with the problem of organizing teaching practice at the Pedagogical Institute of Vasyl Stefanyk Precarpathian National University (Ivano-Frankivsk). The author considers teaching practice to be a very important factor that influences and improves skills and abilities to do educational work at primary school. All kinds of teaching practice in the context of future teachersʼ training to do educational work at primary school are analyzed. The peculiarities of all kinds of teaching practice are examined. According to the author the first step of teaching practice forms the motivational component of readiness to do educational work. Motivation is considered to be the most important one in teaching process. The following steps form practical skills to do educational work at primary school. The final step of teaching practice appeals to improve acquired skills and abilities to do educational work. Experimentally checked package of methodical proposals and tasks as well as the author program of teaching practice is presented. The examples of studentsʼ creative works are given. The author shares personal experience of participating in teaching practice and makes conclusions.